A new route to graphene starting from heavily ozonized fullerenes: Part 2—oxidation in air. Issue 1 (2nd January 2016) - Cataldo, Franco; Putz, Mihai V.; Ursini, Ornella; Angelini, Giancarlo; Garcia-Hernandez, D. Anibal; Manchado, Arturo
ABSTRACT: Graphite oxide (GO) and heavily ozonized C60 and C70 fullerenes known as "fullerene ozopolymers" were studied by TGA-FTIR (Thermogravimetry coupled with FT-IR spectroscopy), DTG (Differential Thermogravimetry) and DTA (Differential Thermal Analysis) in air flow. It was found that GO burns at 70°C higher temperature than the fullerene ozopolymers. This different behavior toward the thermal oxidation of GO is due to the size of the oxidized and staked graphene layers which are expected to be significantly larger than those of the fullerene ozopolymers. Furthermore, the latter should necessarily have a buckybowl shaped structure which should favor their reactivity with oxygen.